2010
DOI: 10.1071/py09074
|View full text |Cite
|
Sign up to set email alerts
|

A response to patient-initiated aggression in general practice: Australian professional medical organisations face a challenge

Abstract: Little is known about the incidence, prevalence, and impact of patient-initiated aggression against general practice staff in Australia or how medically related professional organisations respond to this. The few available Australian studies suggest that up to about two-thirds of Australian GPs experience patient-initiated aggression within a 12-month period. This paper reports on relevant professional stakeholder organisations' perceptions of and response to aggression perpetrated against their members workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Although few studies have directly investigated the effect of workplace aggression on medical practitioner workforce participation decisions, the results of the present research are consistent with outcomes identified in cross-profession populations, 17 nurses 9 and medical practitioners. 11,12 The findings are also consistent with the results of service sector research, such as with retail and hospitality workers, where exposure to workplace aggression has been found to present a risk to psychological and physical well being, organisational commitment and turnover intentions. 18,19 However, medical practitioners occupy a unique position in that they predominantly lead the instigation of interventions that aim to improve the health and well being of individuals and communities, in collaboration with other members of the health and social care workforce.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although few studies have directly investigated the effect of workplace aggression on medical practitioner workforce participation decisions, the results of the present research are consistent with outcomes identified in cross-profession populations, 17 nurses 9 and medical practitioners. 11,12 The findings are also consistent with the results of service sector research, such as with retail and hospitality workers, where exposure to workplace aggression has been found to present a risk to psychological and physical well being, organisational commitment and turnover intentions. 18,19 However, medical practitioners occupy a unique position in that they predominantly lead the instigation of interventions that aim to improve the health and well being of individuals and communities, in collaboration with other members of the health and social care workforce.…”
Section: Discussionsupporting
confidence: 80%
“…10 In Australian general practice, workplace aggression was perceived as having a major impact on staff retention, staff shortages and, in the long run, reduced services to local communities. 11 Meanwhile, a recent Finnish study of medical practitioners 12 found that turnover intentions were associated with violence and bullying. The aim of the present study was to determine the extent to which workplace aggression is associated with workforce participation intentions in a large sample of medical practitioners providing clinical services in range of settings in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite revealing of what occurs in health organizations: not every professional knows of the existence of an official policy against violence; and those that do, do not trust its effectiveness. A second coincidence is provided by the study performed by Ceramidas and Parker (2010): in Australia there are not many health organizations that provide their workers with practical assistance or support in dealing with violent incidents (p. 256). It is quite possible what occurs in Australia may not constitute an exception but the norm in many other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence refers to violent acts that are directed toward people at work or on duty [ 1 ]. It encompasses various types of violence, including verbal abuse (VA), aggression, harassment, bullying, and physical violence such as physical assaults (PA) and threats of assault (TA) [ 2 , 3 ]. Patient-initiated workplace violence in healthcare settings has become an increasingly serious problem in many countries [ 4 – 7 ].…”
Section: Introductionmentioning
confidence: 99%